Irmgard Emmelhainz. Jean-Luc Godard’s Political Filmmaking. Palgrave Macmillan, 2019. - Mackenzie Leadston (Studies in 20th & 21st Century Literature, 2020)
Review of Irmgard Emmelhainz. Jean-Luc Godard’s Political Filmmaking. Palgrave Macmillan, 2019.
Keywords: Jean-Luc Godard; militant filmmaking; political filmmaking